2020
DOI: 10.1001/jamanetworkopen.2020.29655
|View full text |Cite|
|
Sign up to set email alerts
|

Multiomics Characterization of Preterm Birth in Low- and Middle-Income Countries

Abstract: This diagnostic/prognostic study describes the use of cell-free transcriptomics, urine metabolomics, and plasma proteomics for identifying the biological measurements associated with preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…This is in line with a recent multi-omics analysis in preterm birth using cell-free RNA and plasma proteomics in preterm birth. 70 After we and other investigators reported the value of aptamer-based SomaLogic assays to predict early 52 and late preeclampsia, 45 in this study, we evaluated this platform to predict preterm birth and found the SomaLogic assay to be of superior value when compared to whole-blood transcriptomics in predicting spontaneous preterm delivery. The plasma proteomics signatures of spontaneous preterm birth identified here have direct implications for the development of future SomaSignal Tests that were demonstrated in other health applications by combining reproducible proteomic signals with machine learning.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is in line with a recent multi-omics analysis in preterm birth using cell-free RNA and plasma proteomics in preterm birth. 70 After we and other investigators reported the value of aptamer-based SomaLogic assays to predict early 52 and late preeclampsia, 45 in this study, we evaluated this platform to predict preterm birth and found the SomaLogic assay to be of superior value when compared to whole-blood transcriptomics in predicting spontaneous preterm delivery. The plasma proteomics signatures of spontaneous preterm birth identified here have direct implications for the development of future SomaSignal Tests that were demonstrated in other health applications by combining reproducible proteomic signals with machine learning.…”
Section: Discussionmentioning
confidence: 84%
“… 69 IL-6 and ANGPT4, a member of the angiopoietins family, were highlighted as predictors of preterm birth based on proteomics analysis of maternal plasma at 8–20 weeks of gestation in a population of women from low- and middle-income countries. 70 …”
Section: Discussionmentioning
confidence: 99%
“…These genes were up-regulated at delivery, and functional analysis identified biological processes related to an immune/inflammatory response to a stimulus. Biomarkers targeting these processes were identified in predictive models based on a whole-blood transcriptome 42 , 89 , 90 . The pro-inflammatory cytokines, IL-1β , CXCL8 , CCL3 , CCL4 , and CCL20 , were among the strongest predictors selected in all iterations of leave-one-out-cross-validation.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics/metabonomics [ 35 ], exosome metabolomics (exometabolomics) [ 35 ], and multi-OMICS approaches [ 36 , 37 ] represent further innovative strategies for (sub-)typing gynecological patients. Finally, phenomics [ 38 ] aims at systematically and comprehensively measuring and quantitatively assessing the human phenome, which is the array of physical, chemical, biochemical, and biophysical traits expressed and/or generated by an individual during its development, adaptation to genetic influences, and environmental stimuli.…”
Section: Gynecology and Omics Datamentioning
confidence: 99%